Fosfatos de cálcio de interesse biológico: importância como biomateriais, propriedades e métodos de obtenção de recobrimentos - Guastaldi, Antonio Carlos [UNESP]; Aparecida, Anahi Herrera [UNESP] (Sociedade Brasileira de Química, 2010)
For decades the Hydroxyapatite (HA) was only bioceramic of calcium phosphate system used for bone replacement and regeneration, due to its similarity to the mineral phase of bones and teeth. Because its slow degradation, other calcium phosphate classified as biodegradable started to awaken interest, such as: amorphous calcium phosphate (ACP), octacalcium phosphate (OCP) and tricalcium phosphate (TCP). This work presents the evolution of the use of other calcium phosphates due to their better solubility than the HA, comparing their main physical-chemical and biological properties. Are also presented the main methods used to obtain bioceramic coatings on metal and polymer surfaces.
Calcium phosphates of biological interest: importance as biomaterials, properties and methods for coatings obtaining
Keywords: biomaterials; calcium phosphates; bioceramics